2015
DOI: 10.1016/j.memsci.2015.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Role of pressure in organic fouling in forward osmosis and reverse osmosis

Abstract: Fundamental understanding of membrane fouling in osmosis-driven membrane processes is important for further deployment of this emerging technology in desalination and wastewater reuse. In this study, we investigated the role of pressure in organic fouling and reversibility in forward osmosis (FO) and reverse osmosis (RO) using alginate as a model organic foulant. Varying contributions of pressure (i.e., osmotic versus hydraulic) to the overall driving force were realized in forward osmosis (FO), pressure-assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(116 citation statements)
references
References 41 publications
5
109
2
Order By: Relevance
“…6 shows no effect of pressure on foulant accumulation rate, even between pressures of 36 and 64.5 barg. This result contrasts with the findings of Xie et al [7] on the effect of pressure in forward osmosis, in which confocal laser scanning microscopy was used to show that thicker foulant layers develop in FO at atmospheric pressure than in RO 2.0% NaCl, 36 barg 3.1% NaCl, 64.5 barg 3.7% NaCl, 64.5 barg Figure 6: Comparison of calculated foulant accumulation in RO tests with feeds of different salinity on membrane coupons of varying permeability at different pressures, showing strong similarity. The cake structural parameter was calculated using the model presented here for the same tests that exhibited differences in flux decline in Fig.…”
Section: Effect Of Feed Salinity In Rocontrasting
confidence: 99%
See 2 more Smart Citations
“…6 shows no effect of pressure on foulant accumulation rate, even between pressures of 36 and 64.5 barg. This result contrasts with the findings of Xie et al [7] on the effect of pressure in forward osmosis, in which confocal laser scanning microscopy was used to show that thicker foulant layers develop in FO at atmospheric pressure than in RO 2.0% NaCl, 36 barg 3.1% NaCl, 64.5 barg 3.7% NaCl, 64.5 barg Figure 6: Comparison of calculated foulant accumulation in RO tests with feeds of different salinity on membrane coupons of varying permeability at different pressures, showing strong similarity. The cake structural parameter was calculated using the model presented here for the same tests that exhibited differences in flux decline in Fig.…”
Section: Effect Of Feed Salinity In Rocontrasting
confidence: 99%
“…Xie et al [7] found a similar result using confocal laser scanning microscopy on alginate gel layers harvested from fouled membranes: when operated under similar conditions with the same initial flux, thicker cake layers developed in FO than in RO; however, that study attributed the thinner layer in RO to compaction by hydraulic pressure. Future work should address whether the disparity in foulant accumulation is solely driven by the difference in flux decline rates of FO and RO systems, or whether other differences contribute as well.…”
Section: Comparison Of Ro and Fomentioning
confidence: 66%
See 1 more Smart Citation
“…Water flux was continuously monitored throughout the fouling 120 experiments by a data logger. A baseline experiment (i.e., feed without silica foulant) was also 121 carried out to correct the flux decline due to the continuous concentration of the feed solution 122 and dilution of the draw solution, as described in our previous publication (Xie et al 2015b). The 123 feed solution was continuously sampled to quantify the evolution of silica polymerisation.…”
Section: Fo Setup and Silica Scaling Experimental Protocol 99mentioning
confidence: 99%
“…The cross-flow velocity during this stage was 0.11 m/s. The same TMP of 0.45 MPa was chosen to exclude the impact of TMP on membrane fouling (Xie et al, 2015). Alginate was used as a model macromolecule for the fouling experiment.…”
Section: Anti-fouling Property Testmentioning
confidence: 99%